Tax competition and the political economy of public employment: a model for Austria - Michael Christl; Monika Köppl-Turyna (Agenda Austria, 2017)
In this work we simulate the effects of tax autonomy of the Austrian states on the levels of public employment in each state. We show that depending on the strength of the public sector lobby, tax autonomy would require reduction of employment in the public sector between 25% and 35% of the current level. We also show that tax autonomy increases welfare levels by 1% to 1.5%, that is that the positive change in the disposable income of the workers more than offsets the welfare loss resulting from lower public goods` provision. Finally, we show that reduction of public employment is welfare-superior to an alternative scenario, in which employment levels are held constant but the wage levels in the public sector need to be adjusted.
Keywords: D72; H71; H77; 330; Tax competition; Lobbying; Probabilistic voting; Austria